2015
DOI: 10.1103/physrevb.92.115418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gate voltage on spin transport alongα-helical protein

Abstract: Recently, the chiral-induced spin selectivity in molecular systems has attracted extensive interest among the scientific communities. Here, we investigate the effect of the gate voltage on spin-selective electron transport through the α-helical peptide/protein molecule contacted by two nonmagnetic electrodes. Based on an effective model Hamiltonian and the Landauer-Büttiker formula, we calculate the conductance and the spin polarization under an external electric field which is perpendicular to the helix axis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…t j,i represents the intra-chain hopping integral between the sites n and (n + i), and it becomes 26,41 t j,i = t j,1 e −(lj,i−lj,1)/lc…”
Section: Double Stranded Helical Geometry and Tb Hamiltonianmentioning
confidence: 99%
“…t j,i represents the intra-chain hopping integral between the sites n and (n + i), and it becomes 26,41 t j,i = t j,1 e −(lj,i−lj,1)/lc…”
Section: Double Stranded Helical Geometry and Tb Hamiltonianmentioning
confidence: 99%
“…While tight-binding and first-principles theoretical descriptions of a related effect, spin splitting in surface states of Au (111) surfaces induced by Rashba SOC, 22 can yield quantitative accuracy, 23,24 such tight-binding [25][26][27][28][29][30][31][32][33][34][35] and first-principles 36,37 descriptions of the CISS effect so far underestimate it by several orders of magnitude. 38,39 It has been suggested that this discrepancy is due to dephasing 25,29 or local leakages, 35 which can be modeled in terms of Büttiker probes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, subjecting a nanohelix to a transverse electric field (normal to the helix axis) gives rise to superlattice behaviour such as Bragg scattering of electrons on a super-periodic potential, leading to an energy splitting at the edge of the superlattice Brillouin zone between the lowest states linearly tunable by the electric field [42, 43]. This behaviour may result in Bloch oscillations and negative differential conductance [44, 45], and can emphasize spin-polarized transport through helices [31, 46], as well as yield a circular dichroism enhancement useful in nanophotonic chiroptical applications [47]. This system constitutes a unary superlattice and further opens the possibility to use nanohelices as either tunnel diodes or Gunn diodes for frequency multiplying, amplification, and generation or absorption of radiation in the eulogized terahertz range [4851].…”
Section: Introductionmentioning
confidence: 99%